Sistem Pendukung Keputusan Pemilihan Mobil Bekas Dengan Metode Analythical Hierarchy Process Pada CV. Icha Mobilindo - Widyastuti, Ika; Roestam , Rusdianto (Jurnal Manajemen Sistem Informasi, 2022)
Icha Mobilindo is a company engaged in the sale of used cars and has several branches in the city of Jambi. And now there is a problem, namely the process of selecting the best used car, there is no computerized system and not yet using a decision support system method so that the selection of the best used car cannot be measured, and due to the large number of available car choices, consumers are confused about choosing based on the criteria they want. Therefore, this study aims to provide a solution to the problems that occur by offering a decision support system for the selection of used cars using the analytical hierarchy process method. The author develops the system with the prototype method and uses a unified model language system model approach using use case diagrams, activity diagrams and class diagrams. The new system produces output that can display existing used car data, admin data, criteria data, alternative data, used car assessment data and used car ranking results with the analytical hierarchy process method that contributes to the company to increase sales.